TEACHING LISTENING - Nematullayeva Gulsanam Mahmudjon qizi.; Ahmedova Matluba Ibragimjonovna. (Ta’limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2023)
Annotation: During communication a listener switch analyzers to perceive and understand the message. When we say «Did you listen?» we try to analyze did he understand or not. In one word «listening comprehension» means to understand message. Perception and comprehension of the message go simultaneously. We can divide them into different sentences to express different meaning